Quality-yield measure for production processes with very low fraction defective - Pearn, WL; Chang, YC; Wu, CW (My University, 2004)
Process yield is the most common criterion used in manufacturing industry for measuring process performance. A more advanced measurement formula, called the quality yield index, Y-q, is proposed to calculate the quality yield for arbitrary processes by taking customer loss into consideration. Y-q, penalizes yield for the variation of the product characteristics from its target, which presents a measure of the average product loss. Quality yield could be expressed as the traditional yield minus the truncated expected relative loss within the specifications to quantify how well a process can reproduce product items satisfactory to the customers. The paper proposes a reliable approach for measuring quality yield by converting the estimate into a lower confidence bound for processes with a very low fraction of defectives. The lower confidence bound not only provides information about actual process performance that is tightly related to both the fraction of defective units and customer quality loss, but also is useful in making decisions for capability testing.